STRATEGIC SHIFTS IN SOUTH ASIA: US-INDIA RELATIONS AND PAKISTAN’S STRATEGIC REALIGNMENT AND REGIONAL STABILITY - Muhammad Nauman Jalil (International Journal of Contemporary Issues in Social Sciences, 2024)
The geopolitical landscape of South Asia has significantly transformed due to evolving strategic relations between India and the United States with a broad implication on Pakistan. This paper aims to discover Pakistan’s strategic realignment in South Asia due to evolving US-India alliances specifically regarding military and economic ties with China. Additionally, it also analyses the resulting instability in South Asia. Historically ties between the US and Pakistan have changed due to short-term security concerns. The United States no longer prioritizes Pakistan, following American forces’ withdrawal from Afghanistan and the US shift towards India to compensate for the effect of the region in China. There has been increased instability throughout South Asia, particularly regarding the Kashmir conflict between Pakistan and India. Therefore, Pakistan has strengthened its military and financial ties with China, changing results to balance the region in India. Previously, Pakistan used to change to balance the region with U.S. support. Despite less military support, the U.S. still views Pakistan as a regional ally despite its reduced military assistance. Furthermore, India’s opposition to attempts at mediation in the Kashmir issue highlights the difficulties of external involvement in the region. Overall, the growing cooperation of the US with India highlights the need for Pakistan to navigate its relationship with China and the US while tackling regional security issues.